Magnetic resonance imaging detected prostate evasive anterior tumours: Further insights - Al Edawn, Ghazi; Ghai, Sangeet; Margel, David; Kulkarni, Girish; Hamilton, Rob; Toi, Ants; Haidar, Masoom A.; Finelli, Antonio; Fleshner, Neil (Canadian Urological Association Journal, 2015)
Introduction: Clinical confusion continues to exist regarding the underestimation of cancers among patients on active surveillance and among men with repeated negative prostate biopsies despite worrisome prostate-specific antigen (PSA) levels. We have previously described our initial experience with magnetic resonance imaging (MRI)-based detection of tumours in the anterior prostate gland. In this report, we update and expand our experience with these tumours in terms of multiparametric-MRI findings, staging, and grading. Furthermore, we report early treatment outcomes with these unique cancers. Methods: We reviewed our prostate MRI dataset of 1117 cases from January 2006 until December 2012 and identified 189 patients who fulfilled criteria for prostate evasive anterior tumors (PEATS). Descriptive analyses were performed on multiple covariates. Kaplan-Meier actuarial technique was used to plot the treatmentrelated outcomes from PEATS tumours. Results: Among the 189 patients who had MRI-detectable anterior tumours, 148 had biopsy proven disease in the anterior zone. Among these tumours, the average PSA was 18.3 ng/mL and most cancers were Gleason 7. In total, 68 patients chose surgical therapy. Among these men, most of their cancers had extra prostatic extension and 46% had positive surgical margins. Interestingly, upgrading of tumours that were biopsy Gleason 6 in the anterior zone was common, with 59% exhibiting upgrading to Gleason 7 or higher. Biochemical-free survival among men who elected surgery was not ideal, with 20% failing by 20 months. Conclusion: PEATS tumours are found late and are disproportionally high grade tumours. Careful consideration to MRI testing should be given to men at risk for PEATS.